SCIENTIFIC AND THEORETICAL FOUNDATIONS OF IMPLEMENTING INNOVATIVE TECHNOLOGIES IN AGRICULTURE - Kabilova, Madina Abdurazzok kyzy (THE INNOVATION ECONOMY, 2026)
This scientific article comprehensively examines the issue of increasing economic efficiency in the agricultural sector through the implementation of innovative technologies. The research is based on a literature review, within which the scientific works of Uzbek, Russian, and foreign scholars were systematically analyzed. The impact of innovative technologies on agricultural production processes, their role in increasing productivity, reducing production costs, enhancing labor productivity, and ensuring efficient use of resources are thoroughly discussed. The research findings substantiate the significant importance of innovative approaches in ensuring the sustainable development of agriculture.